2021
DOI: 10.4018/ijbsa.20210701.oa3
|View full text |Cite
|
Sign up to set email alerts
|

Gamesy

Abstract: Games have existed since time immemorial and have proved to significantly change people's mentality and attitudes towards countless scenarios. Although games are ‘time wasters', we should acknowledge the one thing that games offer, constant testing, and learning a simple game engages the brain and proves that games are an asset in mental development. Thus, gamification can be used to provide a fun learning environment. In this article, the authors discuss how gamification has been implemented in various applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Waweru W. B., Ng S. Joseph P. and Eaw C. H. developed a gamified learning application, had the respondents use it and conducted surveys and interviews with the respondents. The results showed that the use of gamification could enhance students' intrinsic motivation to learn, but the effectiveness of this enhancement is also limited by the students' own willingness to do so [6]. Nand, K., Baghaei, N., Casey, J., Barmada, B., Mehdipour, F., Liang, H. N. A feature-rich version and a feature-poor version of a game were given to primary school children, and the result was that the feature-rich version was better able to engage children's interests and facilitate their learning [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Waweru W. B., Ng S. Joseph P. and Eaw C. H. developed a gamified learning application, had the respondents use it and conducted surveys and interviews with the respondents. The results showed that the use of gamification could enhance students' intrinsic motivation to learn, but the effectiveness of this enhancement is also limited by the students' own willingness to do so [6]. Nand, K., Baghaei, N., Casey, J., Barmada, B., Mehdipour, F., Liang, H. N. A feature-rich version and a feature-poor version of a game were given to primary school children, and the result was that the feature-rich version was better able to engage children's interests and facilitate their learning [7].…”
Section: Literature Reviewmentioning
confidence: 99%